Developing Wordless Picture Book to Improve the Storytelling Ability of 5 to 6 Years Old Children - Ika Lestari (Jurnal Cakrawala Pendidikan, 2018)
Abstract: This study aims to design and develop a wordless picture book to improve the storytelling ability of level B kindergarten students. This research adopted the design and development model proposed by Lee and Owens (2004). Data collection techniques employed storytelling tests, open-ended questionnaire, interview, and observation. The needs analysis was conducted through a storytelling test. The expert judgment involved media experts, children literature experts, and early childhood instructional design experts to assess the prototype of Wordless Picture Book.  Storytelling test, observation, and interview were used in the try out process. Quantitative data were obtained from pretest and posttest scores and the questionnaire for expert validation. Descriptive qualitative data analysis techniques were used to process the data interviews. Quantitative data analysis was used to examine the scores obtained from the pre and post-tests. The research produced (1) a wordless picture book design and (b) a product of wordless picture book which has been tested for its effectiveness, efficiency, uses, and practicality in improving children’s storytelling ability. Some implications and recommendations are also discussed. Keywords: storytelling, Wordless Picture Book, picture book, early childhood  PENGEMBANGAN WORDLESS PICTURE BOOK UNTUK MENINGKATKAN KEMAMPUAN BERCERITA PADA ANAK USIA 5 – 6 TAHUN Abstrak: Penelitian ini bertujuan untuk menghasilkan desain dan pengembangan produk berupa Wordless Picture Book dalam rangka meningkatkan kemampuan bercerita dari anak TK kelompok B. Metode yang digunakan dalam penelitian ini adalah desain dan pengembangan dari Lee dan Owens (2004). Teknik pengumpulan data menggunakan tes bercerita, kuesioner terbuka, wawancara, dan observasi. Data yang diperoleh melalui analisis kebutuhan dengan mengukur tes bercerita. Validasi ahli dengan instrumen kuesioner untuk menilai prototipe Wordless Picture Book oleh ahli media, sastra anak, dan desain pembelajaran PAUD; serta data uji coba melalui instrumen tes kemampuan bercerita, lembar observasi, dan wawancara. Teknik analisis data deskriptif kualitatif digunakan untuk mengolah data hasil wawancara. Data kuantitatif diperoleh dari hasil pretes dan posttest kepada anak ketika tes bercerita dan kuesioner untuk validasi ahli. Analisis data pada data kuantitatif akan digunakan desain eksperimen pre-experimental designs dengan one group pretest-posttest design. Hasil penelitian menghasilkan sebuah desain dan pengembangan produk Wordless Picture Book yang telah teruji efektivitas, efisiensi, kegunaan, dan kemudahannya dalam meningkatkan kemampuan bercerita anak. Penelitian ini berimplikasi pada dihasilkannya suatu cara di dalam mendesain dan mengembangkan Wordless Picture Book yang mampu meningkatkan kemampuan bercerita anak usia dini. Kata kunci : bercerita, Wordless Picture Book, buku bergambar, anak usia dini